2018
DOI: 10.1101/505867
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Unique Evolutionary Trajectory and Dynamic Conformations of DR and IR/DR- coexisting Plastomes of the Early Vascular Plant Selaginellaceae (Lycophyte)

Abstract: 24Both direct repeats (DR) and inverted repeats (IR) are documented in the published 25 plastomes of four Selaginella species indicating the unusual and diverse plastome 26 structure in the family Selaginellaceae. In this study, we newly sequenced complete 27 plastomes of seven species from five main lineages of Selaginellaceae and also re-28 sequenced three species (S. tamariscina, S. uncinata and S. moellendorffii) to explore 29 the evolutionary trajectory of Selaginellaceae plastomes. Our results showed… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(27 citation statements)
references
References 80 publications
2
25
0
Order By: Relevance
“…1 f, Table 1 ). The studies of Zhang et al., 2019 , Zhang et al, 2020 suggested that species in clade E have lower substitution rates and simpler plastome structures, whereas species in clades A–D have higher substitution rates and more complex plastome structures. Our analyses indicate that the frequency of RNA editing in Selaginella plastomes may be positively correlated with the variation in plastome structure and the substitution rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 f, Table 1 ). The studies of Zhang et al., 2019 , Zhang et al, 2020 suggested that species in clade E have lower substitution rates and simpler plastome structures, whereas species in clades A–D have higher substitution rates and more complex plastome structures. Our analyses indicate that the frequency of RNA editing in Selaginella plastomes may be positively correlated with the variation in plastome structure and the substitution rate.…”
Section: Discussionmentioning
confidence: 99%
“…Compared with species in clade D, species in clades A had a relatively lower number of RNA editing sites ( Fig. 1 f, Table 1 ), but more complex plastome structures and an accelerated substitution rate ( Zhang et al., 2019 , Zhang et al, 2020 ). More comprehensive taxon sampling and transcriptomic evidence are needed to illuminate the evolutionary patterns of RNA editing in Selaginella .…”
Section: Discussionmentioning
confidence: 99%
“…Plastomes of ten species of Selaginella were newly sequenced; three of them were selected from sanguinolenta group (Table S1). Two unpublished plastomes of S. nipponica and S. pallidissima from our group (Kang et al unpublished data) and the previously published fourteen Selaginella plastomes (Mower et al, 2019; Smith, 2009; Tsuji et al, 2007; Xu et al, 2018; Zhang et al, 2019; Zhang et al, 2018) were combined in the following analyses. The Selaginella species were selected to ensure even taxon sampling across subgenera in the genus and covered almost all major lineages (Jermy, 1990; Weststrand and Korall, 2016a, b; Zhou et al, 2016; Zhou and Zhang, 2015).…”
Section: Methodsmentioning
confidence: 99%
“…Total genomic DNA was isolated from silica gel dried materials with a modified cetyl trimethylammonium bromide (CTAB) method (Li et al, 2013) and sequenced on an Illumina HiSeq 2500 (Illumina, San Diego, California, USA). Plastomes were de novo assembled following the methods in Zhang et al (2019); Zhang et al (2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation